Film and layered body
By incorporating a cured resin layer with specific peak intensity ratios and treating it with oxygen-containing plasma, the film achieves better adhesion with inorganic layers, enhancing the laminate's durability and performance.
Patent Information
- Application Number
- JP2023113719
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing laminated films, particularly those with a hard coat film and an antireflection layer, suffer from insufficient adhesion between the organic base film and the inorganic layers.
The film includes a base material layer and a cured resin layer with specific peak intensity ratios measured by X-ray photoelectron spectroscopy, and an inorganic layer such as an antireflection layer, where the cured resin layer is treated with oxygen-containing plasma to enhance adhesion.
The enhanced adhesion improves the bonding between the film and the inorganic layer, resulting in a laminate with improved durability and performance.
Smart Images

Figure 2025011541000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a film and a laminate, and more particularly to a film and a laminate including the film. [Background technology]
[0002] In order to reduce the weight and improve the functionality of electronic products, composite materials that combine organic and inorganic materials have been developed. Known examples of composite materials include laminated films that include an organic substrate film and an inorganic layer on the substrate film.
[0003] As such a laminate film, for example, a hard coat film having a film substrate and a hard coat layer in this order, and an antireflection film having an inorganic oxide primer layer and an antireflection layer in this order have been proposed (see, for example, Patent Document 1).
[0004] In Patent Document 1, before forming a primer layer on the hard coat layer, the hard coat layer is subjected to a plasma treatment. By such a treatment, dirt and moisture on the surface of the hard coat film (hard coat layer) can be removed, and the adhesion between the hard coat film and the antireflection layer can be improved. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 2022-65437 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the base film (hard coat film) of Patent Document 1 has a drawback in that it has insufficient adhesion, and therefore the base film (hard coat film) is required to have even better adhesion.
[0007] The present invention provides a film having excellent adhesion, and a laminate including the film. [Means for solving the problem]
[0008] The present invention [1] is provided with a base layer and a cured resin layer in order toward one side in a thickness direction, and a peak intensity I attributable to a C-C bond at 285 eV measured by X-ray photoelectron spectroscopy on one side in the thickness direction of the cured resin layer is CC , Peak intensity I at 289 eV assigned to the COO bond COO , and the peak intensity I of the O1s spectrum located at 532 eV O is a film that satisfies the following formula (1) and the following formula (2). I COO / I CC >0.5 (1) I O / I CC >1.2 (2)
[0009] The present invention [2] includes the film according to the above [1], in which the cured resin layer includes a cured product of an acrylate resin.
[0010] The present invention [3] includes a laminate comprising the film according to the above [1] or [2] and an inorganic layer in that order toward one side in the thickness direction.
[0011] The present invention [4] includes the laminate according to the above [3], in which the inorganic layer is an anti-reflection layer, and the anti-reflection layer includes a plurality of layers having different refractive indices along the thickness direction.
[0012] The present invention [5] includes the laminate according to the above [3], in which the inorganic layer is a conductive layer. Effect of the Invention
[0013] The film of the present invention has a peak intensity I at 285 eV assigned to a C-C bond measured by X-ray photoelectron spectroscopy on one surface in the thickness direction of the cured resin layer. CC , Peak intensity I at 289 eV assigned to the COO bond COO , and the peak intensity I of the O1s spectrum located at 532 eV O However, the following formula (1) and formula (2) are satisfied, and therefore the adhesion can be improved. I COO / I CC >0.5 (1) I O / I CC >1.2 (2)
[0014] The laminate of the present invention includes the film of the present invention and an inorganic layer in this order toward one side in the thickness direction, and therefore has excellent adhesion between the film and the inorganic layer. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 shows one embodiment of the film of the present invention. [Diagram 2] FIG. 2 is a perspective view showing the positional relationship between the low inductance antenna and the intermediate laminate. [Diagram 3] FIG. 3 is a cross-sectional view showing the positional relationship between the low inductance antenna and the intermediate laminate. [Figure 4] FIG. 4 shows one embodiment of the laminate of the present invention. [Diagram 5] FIG. 5 shows an embodiment of the stack in which the inorganic layer is an anti-reflective layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] One embodiment of the film of the present invention will be described with reference to FIG.
[0017] In FIG. 1, the up-down direction of the paper is the up-down direction (thickness direction). The upper side of the paper is the top side (one side in the thickness direction). The lower side of the paper is the bottom side (the other side in the thickness direction). The left-right direction and the depth direction of the paper are surface directions perpendicular to the up-down direction. Specifically, they follow the directional arrows in each figure.
[0018] The film 1 has a film shape (including a sheet shape) with a predetermined thickness. The film 1 extends in a plane direction perpendicular to the thickness direction. The film 1 has a flat upper surface and a flat lower surface. The film 1 is preferably flexible.
[0019] The film 1 preferably has transparency. Specifically, the total light transmittance (JIS K 7375-2008) of the film 1 is, for example, 80% or more, or preferably 85% or more.
[0020] The thickness of the film 1 is, for example, 10 μm or more, preferably 20 μm or more, and more preferably 35 μm or more, and from the viewpoint of handleability in the roll-to-roll method described later, for example, 200 μm or less, preferably 150 μm or less, more preferably 100 μm or less, and even more preferably 60 μm or less.
[0021] The thickness of the film 1 can be measured using a dial gauge (manufactured by PEACOCK, "DG-205").
[0022] The film 1 includes a base material layer 3 and a cured resin layer 4 in this order toward one side in the thickness direction. Specifically, the film 1 includes the base material layer 3 and the cured resin layer 4 disposed directly on the upper surface (one surface in the thickness direction) of the base material layer 3. The film 1 preferably includes the base material layer 3 and the cured resin layer 4.
[0023] <Base material layer> The base layer 3 is a base material for ensuring the mechanical strength of the film 1.
[0024] The base layer 3 has a film shape and is preferably flexible.
[0025] The substrate layer 3 may be, for example, a polymer film.
[0026] Examples of materials for the polymer film include polyester resin, (meth)acrylic resin, olefin resin, polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, polyimide resin, cellulose resin, and polystyrene resin. Examples of polyester resin include polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. Examples of (meth)acrylic resin include polymethyl methacrylate. Examples of olefin resin include polyethylene, polypropylene, and cycloolefin polymer. Examples of cellulose resin include triacetyl cellulose.
[0027] As the material of the polymer film, a cellulose resin is preferable, and a triacetyl cellulose is more preferable.
[0028] The thickness of the base layer 3 is, for example, 10 μm or more, preferably 20 μm or more, more preferably 30 μm or more from the viewpoint of ensuring mechanical strength, and, for example, 200 μm or less, preferably 150 μm or less, more preferably 100 μm or less, and further preferably 50 μm or less from the viewpoint of handleability in the roll-to-roll method described later. A carrier film may be attached to the back surface of the film 1 in order to ensure transportability and handleability of the base layer 3 in the roll-to-roll method process.
[0029] The thickness of the base layer 3 can be measured using a dial gauge (manufactured by PEACOCK, "DG-205").
[0030] The base layer 3 preferably has transparency. Specifically, the total light transmittance (JIS K 7375-2008) of the base layer 3 is, for example, 80% or more, or preferably 85% or more.
[0031] <Cured resin layer> The cured resin layer 4 has a film shape. The cured resin layer 4 is disposed on the entire upper surface of the base layer 3 so as to be in contact with the upper surface of the base layer 3. The cured resin layer 4 is the uppermost layer of the film 1.
[0032] Examples of the cured resin layer 4 include a hard coat layer, an easy adhesion layer, and an anti-blocking (AB) layer. A preferred example of the cured resin layer 4 is a hard coat layer. The hard coat layer is an abrasion protection layer that makes the film 1 less susceptible to abrasions.
[0033] The hard coat layer is a cured product of a hard coat composition containing an acrylate resin, that is, the hard coat layer (cured resin layer 4) contains a cured product of an acrylate resin.
[0034] If the hard coat layer (cured resin layer 4) contains a cured product of an acrylate resin, the peak intensity I CC (See below), peak intensity I at 289 eV assigned to the COO bond COO (see below), and the peak intensity I of the O1s spectrum located at 532 eV O (described below) can be adjusted to ensure that equation (1) described below and equation (2) described below are satisfied.
[0035] The cured product of the acrylate resin is a cured product of the curing component.
[0036] The curing component includes a urethane (meth)acrylate, an oligomer of a urethane (meth)acrylate, and a polyfunctional (meth)acrylic monomer.
[0037] Examples of the polyfunctional (meth)acrylic monomer include tricyclodecane dimethanol diacrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane triacrylate, pentaerythritol tetra(meth)acrylate, and dimethylolpropane tetraacrylate. Examples of the polyfunctional (meth)acrylic monomer include pentaerythritol tri(meth)acrylate. Examples of the polyfunctional (meth)acrylic monomer include pentaerythritol tri(meth)acrylate. Examples of the polyfunctional (meth)acrylic monomer include pentaerythritol triacrylate, more preferably.
[0038] When the curing component contains a urethane (meth)acrylate and / or a urethane (meth)acrylate oligomer and a polyfunctional (meth)acrylic monomer, the content of the urethane (meth)acrylate and / or the urethane (meth)acrylate oligomer is, for example, 30% by mass or more, preferably 40% by mass or more, and, for example, 70% by mass or less, preferably 60% by mass or less, relative to the curing component. The content of the polyfunctional (meth)acrylic monomer is, for example, 30% by mass or more, preferably 40% by mass or more, and, for example, 70% by mass or less, preferably 60% by mass or less, relative to the curing component.
[0039] Examples of the acrylate resin include an ultraviolet-curable acrylate resin and a thermosetting acrylate resin. The acrylate resin is preferably an ultraviolet-curable acrylate resin. If the acrylate resin is an ultraviolet-curable acrylate resin, it can be cured without heating, which can improve the production efficiency of the film 1.
[0040] The content ratio of the acrylate resin in the hard coat composition is, for example, 80 mass % or more, preferably 90 mass % or more, and for example, 99 mass % or less, preferably 96 mass % or less.
[0041] The hard coat composition optionally contains other curable resins (e.g., polyester resins, amide resins, silicone resins, epoxy resins, and melamine resins), particles, initiators (thermal polymerization initiators, photopolymerization initiators), leveling agents, and fillers (e.g., synthetic smectite).
[0042] Examples of the particles include inorganic particles and organic particles. Examples of the inorganic particles include inorganic oxide particles. Examples of the materials of the inorganic oxide particles include silica, alumina, titania, zirconia, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide. Examples of the materials of the organic particles include polymethyl methacrylate, polystyrene, polyurethane, acrylic-styrene copolymer, benzoguanamine, melamine, silicone, and polycarbonate. Examples of the materials of the organic particles include polystyrene and silicone, preferably.
[0043] The content ratio of inorganic particles is preferably low. The lower the content ratio of inorganic particles, the more the scattering of light caused by inorganic particles can be suppressed, and the manufacturing cost can be reduced. The content ratio of inorganic particles in the hard coat composition is, for example, 20 mass% or less, preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 1 mass% or less, particularly preferably 0.5 mass% or less, most preferably 0.2 mass% or less, even 0.1 mass% or less, and even 0.0 mass% from the viewpoint of visibility (described later).
[0044] The hardcoat composition can be diluted, if necessary, with a solvent, such as, for example, butyl acetate, ethyl acetate, toluene, and cyclopentanone.
[0045] When the hard coat composition is diluted with a solvent, the solids concentration is, for example, 10 mass % or more, preferably 30 mass % or more, and for example, 70 mass % or less, preferably 60 mass % or less.
[0046] As will be described in detail later, the hard coat layer is formed by applying a hard coat composition to one surface in the thickness direction of the base layer 3, and drying and curing it as necessary.
[0047] The hard coat layer preferably has transparency. Specifically, the total light transmittance (JIS K 7375-2008) of the hard coat layer is, for example, 80% or more, preferably 85% or more.
[0048] The thickness of the cured resin layer 4 is, for example, 0.5 μm or more, preferably 2 μm or more, more preferably 3 μm or more, and for example, 30 μm or less, preferably 25 μm or less, more preferably 20 μm or less.
[0049] Peak intensity I assigned to C-C bonds at <285 eV CC , Peak intensity I at 289 eV assigned to the COO bond COO , and the peak intensity I of the O1s spectrum located at 532 eV O > The film 1 has a peak intensity I CC , Peak intensity I at 289 eV assigned to the COO bond COO , and the peak intensity I of the O1s spectrum located at 532 eV O satisfies the following formula (1) and formula (2). I COO / I CC >0.5 (1) I O / I CC >1.2 (2)
[0050] If the above formula (1) and formula (2) are satisfied, the adhesion can be improved.
[0051] On the other hand, if the above formula (1) and / or the above formula (2) is not satisfied, the adhesion decreases.
[0052] In order to satisfy the above formulas (1) and (2), the surface of the cured resin layer 4 is subjected to oxygen-LAICP treatment (described later). In the oxygen-LAICP treatment, for example, the conveying speed (described later), the type of LA21 (described later), the oxygen concentration in the vacuum chamber during the oxygen-LAICP treatment (described later), the pressure in the vacuum chamber during the oxygen-LAICP treatment (described later), the frequency and magnitude of the high frequency power applied to the LA21 during the oxygen-LAICP treatment (described later), and the plasma current density during the oxygen-LAICP treatment (described later) are adjusted.
[0053] <Film manufacturing method> The method for producing the film includes a first step of preparing a base layer 3, a second step of disposing a cured resin layer 4 on one surface in the thickness direction of the base layer 3, and a third step of performing a plasma treatment on one surface in the thickness direction of the cured resin layer 4. This method is preferably performed by a roll-to-roll method. In such a case, the conveying speed is, for example, 0.1 m / min or more and, for example, 20.0 m / min or less. In the following description, the case where the cured resin layer 4 is a hard coat layer will be described in detail.
[0054] [1st step] In the first step, the base layer 3 is prepared.
[0055] [Second process] In the second step, a hard coat layer (cured resin layer 4) is disposed on one surface in the thickness direction of the substrate layer 3. To dispose a hard coat layer on one surface in the thickness direction of the substrate layer 3, a hard coat composition is applied to one surface in the thickness direction of the substrate layer 3, and then dried and cured as necessary to form the hard coat layer.
[0056] As for the drying conditions, the drying temperature is, for example, 50° C. or more and, for example, 120° C. or less. The drying time is, for example, 10 seconds or more and, for example, 10 minutes or less.
[0057] When the hard coat composition contains an ultraviolet-curable acrylate resin, the ultraviolet-curable acrylate resin is cured by ultraviolet irradiation. Examples of the light source for ultraviolet irradiation include a high-pressure mercury lamp and an LED light. The cumulative irradiation amount of ultraviolet light is, for example, 100 mJ / cm. 2 or more, for example, 500 mJ / cm 2 The following is the result.
[0058] When the hard coat composition contains a thermosetting acrylate resin, the thermosetting acrylate resin is cured by heating. The heating temperature is, for example, 100° C. or more and, for example, 150° C. or less. The heating time is, for example, 10 seconds or more and, for example, 10 minutes or less.
[0059] In this way, the hard coat layer (cured resin layer 4) is disposed on one surface in the thickness direction of the base layer 3, and an intermediate laminate 2 including the base layer 3 and the hard coat layer (cured resin layer 4) in this order is produced.
[0060] [3rd step] In the second step, one surface in the thickness direction of the hard coat layer (cured resin layer 4) is subjected to a plasma treatment.
[0061] Specifically, the plasma treatment includes a treatment using inductively coupled plasma of an oxygen-containing gas (oxygen-LAICP treatment) generated by applying high-frequency power to a low-inductance antenna.
[0062] The low inductance antenna means an antenna that has a low inductance of 7.5 μH or less and is capable of generating inductively coupled plasma by application of high frequency power.
[0063] 2 and 3, the low inductance antenna 21 (LA21) is supported by a mounting fixture 22 and arranged in a state of being covered by a cover block 23 (omitted in FIG. 3) (a case where the number of LA21 is four is illustrated as an example). The multiple LA21 are arranged in an array so as to be aligned in the running direction of the intermediate laminate 2 and in a direction perpendicular to the running direction (the width direction of the intermediate laminate 2).
[0064] The LA21 is formed of a conductor. Examples of the conductor include copper and silver, and preferably copper. The LA21 may be covered with an insulator. Examples of the insulator include glass and quartz.
[0065] The LA 21 is electrically connected to a high-frequency power source (RF power source) via an impedance matching box.
[0066] The LA21 has an open loop shape. The open loop shape of the LA21 can reduce the inductance of the LA21. Therefore, the open loop shape of the LA21 can suppress an increase in voltage caused by an increase in power applied to the LA21. This can suppress abnormal discharge during plasma processing. Suppressing abnormal discharge can suppress damage to the intermediate laminate 2 being plasma processed.
[0067] Specifically, the LA 21 has a U-shape with two free ends. For each LA 21, the two free ends are fixed to the fixture 22 so as to be aligned in the width direction of the intermediate laminate 2. More specifically, the LA 21 is fixed to the fixture 22 via a feedthrough 24 as shown in FIG.
[0068] Moreover, the LA 21 has an extension portion 21a on the side opposite to the two free ends. The extension portion 21a extends in the width direction of the intermediate laminate 2. Each extension portion 21a may extend in the running direction of the intermediate laminate 2 (two LAs 21 may be arranged in this manner).
[0069] The LA21 extends from the fixture 22 toward the intermediate laminate 2. The LA21 extends in a direction perpendicular to the fixture 22. The extension length d1 of the LA21 from the fixture 22 is, for example, 30 mm or more and, for example, 150 mm or less.
[0070] The maximum length d2 of the LA21 in the planar direction of the intermediate laminate 2 is, for example, 50 mm or more and, for example, 150 mm or less.
[0071] The separation distance d3 between the LA 21 and the intermediate laminate 2 is, for example, 50 mm or more, and, for example, 200 mm or less.
[0072] Preferably, the extension length d1 and the separation distance d3 are the same.
[0073] The ratio (d3 / d1) of the separation distance d3 to the extension length d1 is, for example, not less than 0.5 and not more than 3.5.
[0074] The center-to-center distance d4 between adjacent LAs 21 in the running direction of the intermediate laminate 2 is, for example, 100 mm or more, and, for example, 500 mm or less. The number (number of rows) of LAs 21 spaced apart in the running direction of the intermediate laminate 2 may be 1, 2 or 3 depending on the running speed of the intermediate laminate 2 (i.e., plasma treatment time), or may be 4 or more if necessary.
[0075] The center-to-center distance d5 between adjacent LAs 21 in the width direction of the intermediate stack 2 is, for example, 200 mm or less, or, for example, 500 mm or less. The uniformity of the plasma density in the width direction of the intermediate stack 2 can be controlled.
[0076] Preferably, the center distance d4 and the center distance d5 are the same.
[0077] The centers of the extensions 21a of the four LAs 21 preferably form a square with the vertices as vertices. Such a set of LAs 21 can generate high density plasma with high in-plane uniformity. For example, the high frequency antenna for plasma generation described in JP 2013-258153 A can be used as the LA 21.
[0078] Also, the LA21 may have a coil shape instead of an open loop shape.
[0079] The cover block 23 includes a block body 23A and a plurality of partition plates 23B. The block body 23A has a plurality of storage spaces 23a. Each storage space 23a stores one LA 21. The partition plates 23B are arranged to close the storage space 23a. The storage space 23a is an enclosed space. In the cover block 23, the block body 23A is made of, for example, aluminum. An example of the aluminum is aluminum A5052. The partition plates 23B are made of an insulating material. An example of the insulating material is quartz and glass. The separation distance d' (shown in FIG. 3) between the traveling intermediate stack 2 and the cover block 23 is, for example, 50 mm or more, and, for example, 200 mm or less. Such a cover block 23 helps to avoid damage and contamination of the LA21 due to plasma processing without excessively reducing the plasma conversion efficiency due to the power applied to the LA21, and also helps to suppress damage to the intermediate laminate 2 being plasma processed.
[0080] In the oxygen-LAICP process, the LA 21 is placed in a vacuum chamber, and the intermediate laminate 2 is transported thereinto, and oxygen is supplied into the vacuum chamber.
[0081] From the viewpoint of improving adhesion, the oxygen concentration in the vacuum chamber is, for example, 30 vol.% or more, more preferably 50 vol.% or more, and even more preferably 80 vol.% or more, and from the viewpoint of improving adhesion, it is, for example, 100 vol.% or less, preferably 95 vol.% or less, and more preferably 90 vol.% or less.
[0082] In addition, an inert gas or an active gas other than oxygen may be introduced into the vacuum chamber. Examples of the inert gas include rare gases (argon, krypton, and xenon). Examples of the active gas include nitrogen and water vapor.
[0083] The pressure in the vacuum chamber during the oxygen-LAICP treatment is, for example, 0.1 Pa or more, preferably 0.2 Pa or more, more preferably 0.3 Pa or more, and for example, 7.0 Pa or less, preferably 5.0 Pa or less, more preferably 3.0 Pa or less, and further preferably 1.0 Pa or less. The pressure can be adjusted by the amount of oxygen supplied to the vacuum chamber.
[0084] In addition, the frequency of the high-frequency power applied to LA21 during oxygen-LAICP treatment is, for example, 1 MHz or more, preferably 3 MHz or more, more preferably 5 MHz or more, even more preferably 10 MHz or more, and for example, 100 MHz or less, preferably 80 MHz or less, more preferably 60 MHz or less.
[0085] The high frequency power is, for example, 1.0 kW or more, preferably 1.5 kW or more, more preferably 1.8 kW or more, and for example, 10 kW or less, preferably 8 kW or less, more preferably 6 kW or less.
[0086] In the oxygen-LAICP process, the plasma current density at the intermediate position between the LA 21 and the intermediate laminate 2 is, for example, 1.0 mA / cm 3 More than 2.0 mA / cm 3 More preferably, 3.0 mA / cm 3 More preferably, 4.0 mA / cm 3 or more, for example, 10mA / cm 3 Less than or equal to 8mA / cm 3 Less than or equal to 5 mA / cm, more preferably 3 The following is the result.
[0087] The plasma current density can be adjusted by the amount of oxygen introduced, the frequency of the high frequency power, and the high frequency power.
[0088] In this way, one surface in the thickness direction of the hard coat layer (cured resin layer 4) is subjected to plasma treatment, and the film 1 is produced.
[0089] <Laminate> As shown in FIG. 4, laminate 10 comprises film 1 (specifically, film 1 of the above-mentioned first embodiment or film 1 of the above-mentioned second embodiment) and inorganic layer 11, in that order toward one side in the thickness direction (note that FIG. 4 shows the case where film 1 is film 1 of the above-mentioned second embodiment). Specifically, laminate 10 comprises film 1 and inorganic layer 11 disposed directly on the upper surface (one side in the thickness direction) of film 1. Laminate 10 preferably comprises film 1 and inorganic layer 11.
[0090] [film] The film 1 is disposed over the entire lower surface of the inorganic layer 11 so as to be in contact with the lower surface of the inorganic layer 11. The film 1 is the lowermost layer in the laminate .
[0091] [Inorganic layer] The inorganic layer 11 has a film shape. The inorganic layer 11 is disposed on the entire upper surface of the film 1 so as to be in contact with the upper surface of the film 1. The inorganic layer 11 is the uppermost layer in the laminate 10.
[0092] Examples of the inorganic layer 11 include an anti-reflection layer and a conductive layer. Hereinafter, the cases where the inorganic layer 11 is an anti-reflection layer and a conductive layer will be described in detail.
[0093] (When the inorganic layer is an anti-reflection layer) With reference to FIG. 5, the case where the inorganic layer 11 is an anti-reflection layer will be described in detail.
[0094] When the inorganic layer 11 is an anti-reflection layer, the laminate 10 is an anti-reflection film.
[0095] The antireflection layer includes a plurality of layers having different refractive indices along the thickness direction. Specifically, the antireflection layer includes high refractive index layers having a relatively high refractive index and low refractive index layers having a relatively low refractive index alternately in the thickness direction. In the antireflection layer, the net reflected light intensity is attenuated by the interference between reflected light at a plurality of interfaces in the plurality of thin layers (high refractive index layers, low refractive index layers) included therein. In addition, in the antireflection layer, the interference effect of attenuating the reflected light intensity can be exerted by adjusting the optical film thickness (product of refractive index and thickness) of each thin layer. Such an antireflection layer includes high refractive index layers 12 and low refractive index layers 13 alternately in order toward one side in the thickness direction.
[0096] The antireflection layers (specifically, the high refractive index layer 12 and the low refractive index layer 13) preferably contain one selected from the group consisting of metals, alloys, metal oxides, metal nitrides, and metal fluorides, and more preferably contain one selected from the group consisting of metals, metal oxides, and metal nitrides, so that the antireflection layers can suppress the reflection intensity of external light.
[0097] Examples of metals include silicon, nickel, chromium, aluminum, tin, gold, silver, platinum, zinc, titanium, tungsten, zirconium, niobium, and palladium. Examples of alloys include alloys of the above metals. Examples of metal oxides include metal oxides of the above metals. Examples of metal nitrides include metal nitrides of the above metals. Examples of metal fluorides include metal nitrides of metal fluorides of the above metals.
[0098] In particular, the material used for the anti-reflective layer is selected depending on the desired refractive index.
[0099] Specifically, examples of the high refractive index material constituting the high refractive index layer 12 include niobium oxide (Nb2O5), titanium oxide, zirconium oxide, indium tin oxide (ITO), and antimony-doped tin oxide (ATO). As the high refractive index material, indium tin oxide (ITO) is preferable.
[0100] Examples of the low refractive index material constituting the low refractive index layer 13 include silicon dioxide (SiO2) and magnesium fluoride. As the low refractive index material, silicon dioxide (SiO2) is preferably used.
[0101] In the antireflection layer, the high refractive index layer 12 has a thickness of, for example, 1 nm or more, preferably 3 nm or more, and for example, 15 nm or less, preferably 10 nm or less.
[0102] Moreover, the thickness of the low refractive index layer 13 is thicker than the thickness of the high refractive index layer 12, and is, for example, more than 15 nm and, for example, 50 nm or less, preferably 30 nm or less.
[0103] The ratio of the thickness of the low refractive index layer 13 to the thickness of the high refractive index layer 12 (thickness of the low refractive index layer 13 / thickness of the high refractive index layer 12) is, for example, more than 1, preferably 2 or more, more preferably 3 or more, and for example, 10 or less, preferably 5 or less.
[0104] The thickness of the antireflection layer is, for example, 20 nm or more, and, for example, 300 nm or less, preferably 250 nm or less, and more preferably 200 nm or less.
[0105] When the inorganic layer 11 is an anti-reflective layer, the laminate 10 can be produced by disposing the anti-reflective layer on one surface of the film 1 in the thickness direction by a known sputtering method.
[0106] In the antireflection layer, the number of high refractive index layers and low refractive index layers is not particularly limited.
[0107] (When the inorganic layer is a conductive layer) When the inorganic layer 11 is a conductive layer, the laminate 10 is a transparent conductive film.
[0108] Examples of materials for the conductive layer include metals and metal oxides. Examples of metals include copper, silver, gold, nickel, chromium, and alloys thereof. Examples of metal oxides include indium-containing conductive oxides and antimony-containing conductive oxides. Examples of indium-containing conductive oxides include indium tin composite oxide (ITO), indium zinc composite oxide (IZO), indium gallium composite oxide (IGO), and indium gallium zinc composite oxide (IGZO). Examples of antimony-containing conductive oxides include antimony tin composite oxide (ATO).
[0109] The conductive layer has a thickness of, for example, 1 nm or more, preferably 5 nm or more, and for example, 100 nm or less.
[0110] When the inorganic layer 11 is a conductive layer, the laminate 10 can be produced by disposing a conductive layer on one surface of the film 1 in the thickness direction by a known sputtering method.
[0111] <Action and effect> The film 1 has a peak intensity I CC , Peak intensity I at 289 eV assigned to the COO bond COO , and the peak intensity I of the O1s spectrum located at 532 eV O satisfies the above formula (1) and formula (2), and therefore the adhesion can be improved.
[0112] For details, see the above peak intensity I COO is the intensity of the peak assigned to the COO bond, and the above peak intensity I Ois the intensity of the peak in the O1s spectrum. Both of these peaks are due to bonds containing oxygen.
[0113] On the other hand, the above peak intensity I CC is a peak that is assigned to a C—C bond and is derived from a bond that does not contain oxygen.
[0114] In addition, the above peak intensity I CC , the above peak intensity I COO , and the above peak intensity I O is a peak intensity derived from one surface of the cured resin layer 4 in the thickness direction, since it is measured for one surface of the cured resin layer 4 in the thickness direction by using X-ray photoelectron spectroscopy.
[0115] Satisfying the above formula (1) or (2) means that on one surface in the thickness direction of cured resin layer 4, the proportion of bonds containing oxygen is higher than the proportion of bonds not containing oxygen.
[0116] Since the ratio of bonds containing oxygen is high, it is presumed that oxygen modification is performed on the surface of the cured resin layer 4. As a result, the film 1 (cured resin layer 4) and the inorganic layer 11 are chemically bonded via oxygen, improving adhesion.
[0117] The laminate 10 includes the film 1 and the inorganic layer 11 in this order toward one side in the thickness direction. Therefore, the adhesion between the film 1 and the inorganic layer 11 is excellent. EXAMPLES
[0118] The present invention will be described in more detail below with reference to examples and comparative examples. The present invention is not limited to the examples and comparative examples. The specific numerical values of the blending ratio (content ratio), physical property values, parameters, etc. used in the following description can be replaced with the upper limit values (numerical values defined as "less than or equal to" or "less than") or lower limit values (numerical values defined as "more than or equal to" or "exceeding") of the corresponding blending ratio (content ratio), physical property values, parameters, etc. described in the above "Form for carrying out the invention".
[0119] Example 1 <Film manufacturing> [1st step] In the first step, a base layer was prepared. Specifically, a long TAC film (triacetyl cellulose film, length 100 m, width 340 mm, thickness 40 μm) was first prepared as the base layer.
[0120] [Second process] In the second step, a hard coat layer (cured resin layer) was disposed on one surface in the thickness direction of the substrate layer. Specifically, first, 100 parts by mass (solid content equivalent value) of a butyl acetate solution of urethane acrylate (product name "Luxidia 17-806", solid content concentration 80% by mass, manufactured by DIC Corporation), 5 parts by mass of a photopolymerization initiator (product name "Omnirad907", manufactured by IGM Resins), 0.03 parts by mass of a leveling agent (product name "GRANDIC PC4100", manufactured by DIC Corporation), and butyl acetate as a solvent were mixed to adjust the solid content concentration to 75% by mass. Next, cyclopentanone was added as a solvent to prepare a hard coat composition (solid content concentration 50% by mass).
[0121] Next, a hard coat composition was applied to one surface of the substrate layer in the thickness direction to form a coating film. Next, the coating film was dried by heating and then cured by UV irradiation. As a result, a hard coat layer (thickness 5 μm) was disposed on one surface of the substrate layer in the thickness direction.
[0122] The heating temperature was 100° C., and the heating time was 60 seconds. For ultraviolet irradiation, a high-pressure mercury lamp was used as the light source, and ultraviolet rays with a wavelength of 365 nm were irradiated onto the coating film, with an integrated irradiation amount of 300 mJ / cm 2 . 2 It was decided.
[0123] In this manner, an intermediate laminate having the base layer and the hard coat layer (cured resin layer) in that order was produced.
[0124] [3rd step] In the third step, one surface in the thickness direction of the hard coat layer was subjected to a plasma treatment.
[0125] Specifically, the intermediate laminate was transported into a vacuum chamber at a transport speed of 1.0 m / min by a roll-to-roll method under vacuum, and the intermediate laminate was subjected to a plasma treatment.
[0126] The plasma treatment was performed using oxygen-LAICP. The low-inductance antenna shown in Figures 2 and 3 was used.
[0127] In the low inductance antenna, the extension length d1 is 88 mm, the maximum length d2 is 100 mm, the separation distance d3 is 112 mm, the center distance d4 is 290 mm, the center distance d5 is 280 mm, and the separation distance d' is 100 mm. Each low inductance antenna is electrically connected to a high frequency power source (RF power source, frequency 13.56 MHz) via an impedance matching device.
[0128] The ultimate vacuum of the vacuum chamber is 1.0×10 -4After evacuating the inside of the device until the pressure reached 0.5 Pa, oxygen gas (oxygen concentration 100% by volume) was introduced into the vacuum chamber, and the pressure inside the vacuum chamber was set to 0.5 Pa. By applying high frequency power of 5.0 kW to the four low inductance antennas by a high frequency power source, an inductively coupled plasma of an oxygen-containing gas was formed around the antennas (the hard coat layer was treated with this plasma). The plasma current density at the midpoint between the low inductance antennas and the intermediate laminate was set to 4.2 mA / cm. 3 It was decided.
[0129] In this way, a film was produced.
[0130] <Production of Laminate> An anti-reflection layer was formed by sputtering on one surface in the thickness direction of the film.
[0131] Specifically, after evacuating the vacuum chamber, -4 The pressure was reduced to 100 Pa, argon gas was introduced as a sputtering gas, and a high refractive index layer (ITO film, thickness 5 nm) was placed on an ITO target (SnO ratio 10 mass%, length 600 mm x width 150 mm x thickness 5 mm, single cathode system) (input power 1.0 kW, deposition chamber pressure: 0.3 Pa, DC discharge). Next, a low refractive index layer (SiO2 film, thickness 20 nm) was placed on a pure Si target (length 600 mm x width 50 mm x thickness 5 mm, dual cathode system) (input power: 3.0 kW, deposition pressure 0.3 Pa, O2 / Ar=0.3, MFAC power supply 60 kHz).
[0132] In this way, a laminate was produced.
[0133] Comparative Example 1 <Film manufacturing> An intermediate laminate was prepared based on the same procedures as in the first and second steps of Example 1.
[0134] In the third step, one surface in the thickness direction of the hard coat layer was subjected to a bombardment treatment with argon ions.
[0135] Specifically, the intermediate laminate was transported to a vacuum chamber at a transport speed of 1.0 m / min by a roll-to-roll method under vacuum.
[0136] The vacuum chamber is equipped with a pair of flat electrodes for generating plasma, a cathode electrode and an anode electrode (both rectangular electrodes made of SUS304). The pair of flat electrodes are arranged with a gap of 50 mm between them, parallel to the intermediate laminate passing through the vacuum chamber. The anode electrode is arranged so as to be in constant contact with the intermediate laminate passing through the vacuum chamber, and is grounded outside the vacuum chamber. The cathode electrode is arranged at a position 35 mm away from the intermediate laminate, and is electrically connected to a high-frequency power source (RF power source, 13.56 MHz) via an impedance matching device. The length of each electrode in the film running direction is 110 mm, and the length in the width direction is 430 mm.
[0137] The ultimate vacuum of the vacuum chamber is 1.0×10 -4 After evacuating the inside of the device until the pressure reached 0.5 Pa, argon gas was introduced as an inert gas into the vacuum chamber, and the pressure in the vacuum chamber was set to 0.5 Pa. Capacitively coupled plasma (CCP) was generated by applying 550 W of power between the flat electrodes by a high-frequency power source. In this plasma environment, the surface of the hard coat layer was bombarded with argon ions. <Production of Laminate> A laminate was produced according to the same procedure as in Example 1.
[0138] Comparative Example 2 An intermediate laminate was prepared based on the same procedures as the first and second steps of Example 1. Thereafter, the third step was not performed. Thereafter, a laminate was prepared based on the same procedures as Example 1.
[0139] Example 2 <Film manufacturing> [1st step] Based on the same procedure as in Example 1, a base layer was prepared.
[0140] [Second process] In the second step, a hard coat layer (cured resin layer) was arranged on one surface in the thickness direction of the base layer. Specifically, 50 parts by mass of pentaerythritol triacrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., product name "Viscoat #300"), 50 parts by mass of urethane acrylate prepolymer (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product name "UA-53H-80BK"), 3.5 parts by mass of silicone particles (manufactured by Momentive Performance Materials Japan LLC, product name "Tospearl 130", weight average particle size: 3 μm, refractive index: 1.42), 2 parts by mass of synthetic smectite (organic clay, manufactured by Co-op Chemical Co., Ltd., trade name "Lucentite SAN"), 3 parts by mass of photopolymerization initiator (manufactured by BASF, trade name "Irgacure 907"), and 0.2 parts by mass of leveling agent (manufactured by DIC Corporation, trade name "PC4100", solid content concentration 10%) were mixed and diluted with a toluene / cyclopentanone (CPN) mixed solvent (mass ratio 70 / 30) to prepare a hard coat composition (solid content concentration 35% by mass). The synthetic smectite was used by diluting it with toluene so that the solid content concentration became 6% by mass.
[0141] Next, a hard coat composition was applied to one surface of the substrate layer in the thickness direction to form a coating film. Next, the coating film was dried by heating and then cured by UV irradiation. As a result, a hard coat layer (thickness 6.3 μm) was disposed on one surface of the substrate layer in the thickness direction.
[0142] The heating temperature was 80° C., and the heating time was 60 seconds. For ultraviolet irradiation, a high-pressure mercury lamp was used as a light source, and ultraviolet rays with a wavelength of 365 nm were irradiated onto the coating film, with an integrated irradiation amount of 300 mJ / cm 2 . 2 It was decided.
[0143] In this manner, an intermediate laminate having the base layer and the hard coat layer (cured resin layer) in that order was produced.
[0144] [3rd step] In the third step, based on the same procedure as in Example 1, one surface in the thickness direction of the hard coat layer was subjected to plasma treatment.
[0145] <Production of Laminate> A laminate was produced according to the same procedure as in Example 1.
[0146] Comparative Example 3 <Film manufacturing> An intermediate laminate was prepared based on the same procedures as in the first and second steps of Example 2.
[0147] In the third step, based on the same procedure as in Comparative Example 1, one surface in the thickness direction of the hard coat layer was subjected to a bombardment treatment with argon ions.
[0148] <Production of Laminate> A laminate was produced according to the same procedure as in Example 1.
[0149] Comparative Example 4 An intermediate laminate was prepared based on the same procedures as the first and second steps of Example 2. Thereafter, the third step was not performed. Thereafter, a laminate was produced based on the same procedures as Example 1.
[0150] Example 3 <Film manufacturing> [1st step] Based on the same procedure as in Example 1, a base layer was prepared.
[0151] [Second process] In the second step, a hard coat layer (cured resin layer) was placed on one surface in the thickness direction of the base layer. Specifically, first, 50 parts by weight of pentaerythritol triacrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., product name "Viscoat #300"), 50 parts by weight of urethane acrylate prepolymer (manufactured by Shin-Nakamura Chemical Co., Ltd., product name "UA-53H-80BK"), 1.7 parts by weight of silicone particles (manufactured by Momentive Performance Materials Japan, LLC, product name "Tospearl 130", weight average particle size: 3 μm, refractive index: 1.42), and 1.7 parts by weight of polystyrene particles (manufactured by Sekisui Chemical Co., Ltd., product name "Techpolymer ", weight average particle size: 3 μm, refractive index: 1.59) 2.3 parts by weight, synthetic smectite (organic clay, manufactured by Co-op Chemical Co., Ltd., trade name "Lucentite SAN") 2 parts by weight, photopolymerization initiator (manufactured by BASF, trade name "Irgacure 907") 3 parts by weight, and leveling agent (manufactured by DIC Corporation, trade name "PC4100", solid content concentration 10%) 0.2 parts by weight were mixed and diluted with a toluene / cyclopentanone (CPN) mixed solvent (weight ratio 70 / 30) to prepare a hard coat composition (solid content concentration 35% by mass). The synthetic smectite was used by diluting it with toluene so that the solid content concentration was 6% by mass.
[0152] Next, a hard coat composition was applied to one surface of the substrate layer in the thickness direction to form a coating film. Next, the coating film was dried by heating and then cured by UV irradiation. As a result, a hard coat layer (thickness 6.3 μm) was disposed on one surface of the substrate layer in the thickness direction.
[0153] The heating temperature was 80° C., and the heating time was 60 seconds. For ultraviolet irradiation, a high-pressure mercury lamp was used as a light source, and ultraviolet rays with a wavelength of 365 nm were irradiated onto the coating film, with an integrated irradiation amount of 300 mJ / cm 2 . 2 It was decided.
[0154] In this manner, an intermediate laminate having the base layer and the hard coat layer (cured resin layer) in that order was produced.
[0155] [3rd step] In the third step, based on the same procedure as in Example 1, one surface in the thickness direction of the hard coat layer was subjected to plasma treatment.
[0156] <Production of Laminate> A laminate was produced according to the same procedure as in Example 1.
[0157] Comparative Example 5 <Film manufacturing> An intermediate laminate was prepared based on the same procedures as in the first and second steps of Example 3.
[0158] In the third step, based on the same procedure as in Comparative Example 1, one surface in the thickness direction of the hard coat layer was subjected to a bombardment treatment with argon ions.
[0159] <Production of Laminate> A laminate was produced according to the same procedure as in Example 1.
[0160] Comparative Example 6 An intermediate laminate was prepared based on the same procedures as the first and second steps of Example 3. Thereafter, the third step was not performed. Thereafter, a laminate was produced based on the same procedures as Example 1.
[0161] <Evaluation> [X-ray photoelectron spectroscopy] For the films of each of the Examples and Comparative Examples, narrow scan measurements were carried out on the surface of the hard coat layer near the C1s spectrum and O1s spectrum under the conditions below to obtain spectra. {conditions} Equipment: ULVAC-PHI, Quantera SXM X-ray source: Monochrome Al Kα X-Ray Setting: 100μmφ[15kV, 25W] Photoelectron take-off angle: 45° to the sample surface Neutralization conditions: Use of neutralization gun and Ar ion gun (neutralization mode) Bond energy correction: The peak due to the CC bond in the C1s spectrum is corrected to 285.0 eV.
[0162] The film was cut out from the center of the width direction (340 mm width) into a sample of about 1 cm square.
[0163] Peak intensity I at 285 eV assigned to CC bond CC , Peak intensity I at 289 eV assigned to the COO bond COO , and the peak intensity I of the O1s spectrum located at 532 eV O are shown in Table 1.
[0164] [Adhesion] The laminates of each Example and Comparative Example were cut into a size of 50 mm x 50 mm to prepare samples. Next, cuts were made at 1 mm intervals on the treated surface of the sample to create a grid of 100 squares, and then the sample was placed in a weather resistance tester under the following conditions. {conditions} SUV irradiation conditions Temperature and humidity conditions: 85℃45%Rh Light source used: Metal halide lamp Irradiation conditions: 150mW / cm 2 (290-450nm)
[0165] Next, 2 mL of isopropyl alcohol was continuously dropped onto the surface of the anti-reflective layer to prevent it from drying out, and a polyester wiper (Anticon Gold, manufactured by Sanplatec) fixed to a 20 mm square SUS jig was rubbed over the grid (load: 1.5 kg, 1000 strokes). A grid in which the anti-reflective layer had peeled off over an area of 1 / 4 or more of the grid area was counted as "peeling." The adhesion was evaluated based on the following criteria. The results are shown in Table 1. {standard} ○: Peeling was 5 squares or less. ×: The peeling exceeded 5 squares.
[0166] [Table 1] [Explanation of symbols]
[0167] 1. Film 3 Base material layer 4 Cured resin layer 10 Laminate 11 Inorganic layer
Claims
1. A base material layer and a cured resin layer are provided in this order toward one side in a thickness direction, The peak intensity I attributable to a C-C bond at 285 eV measured by X-ray photoelectron spectroscopy on one side in the thickness direction of the cured resin layer CC , the peak intensity I at 289 eV assigned to the COO bond COO , and the peak intensity I of the O1s spectrum located at 532 eV O A film, which satisfies the following formula (1) and the following formula (2). I COO / I CC >0.5 (1) I O / I CC >1.2 (2)
2. The film according to claim 1 , wherein the cured resin layer comprises a cured product of an acrylate resin.
3. A laminate comprising the film according to claim 1 or 2 and an inorganic layer in that order toward one side in a thickness direction.
4. the inorganic layer is an anti-reflection layer, The laminate according to claim 3 , wherein the antireflection layer comprises a plurality of layers having mutually different refractive indices along a thickness direction.
5. The laminate according to claim 3 , wherein the inorganic layer is a conductive layer.
Citation Information
Patent Citations
Manufacture of metal element-containing thin film laminate
JP2000185362A
Water-repellent oil-repellent antifouling transparent member and method for producing the same, and article using them
JP2010280147A
Laminate, optical member with laminate, and image display device
JP2023040665A
Organic electroluminescent display device and method for manufacturing same
WO2014141734A1
Method for producing optical film, and optical film
WO2016174893A1